The Influence of Leadership, Motivation, and Communication On Employee Performance - Agustina, Mufaalatul; Setyanti, Sri Wahyu Lelly Hana; Farida, Lilik; Titisari, Purnamie (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to see the influence of leadership, motivation, and communication that employees have on the performance of CV employees. Mitra Dunia Palletindo. This research is included in the category of explanatory research because it aims to explain the causal relationship (cause-effect) between variables by testing the hypotheses that have been formulated. The sampling technique used in this study is saturated sampling or census, namely the determination of the sample when all members of the population are used as samples. So the total sample is 50 employees. The type of data used in this research is quantitative qualitative data. Quantitative data is data in the form of numbers or numbers obtained from scores of respondents' answers.